DETERMINASI KEPATUHAN WAJIB PAJAK PEKERJA LEPAS: PERAN PENGETAHUAN PERPAJAKAN, SANKSI, KESADARAN DAN SISTEM E-FILING - Sonia Oktaviana; Khoirina Farina (Universitas Trilogi, 2025)
This study aims to determine and analyze the effect of tax knowledge, tax sanctions, taxpayer awareness, and the implementation of the E-filing system on taxpayer compliance of freelance workers in Bogor Regency. The population in this study was 108 freelance respondents. The sampling technique was purposive sampling by distributing questionnaires via Google Form The analysis method in this study used the Smart PLS analysis tool. The results of this study indicate that the variables of tax knowledge, tax sanctions, taxpayer awareness, and the implementation of the e-filing system have a positive and significant effect on taxpayer compliance of freelance workers. These findings serve as input for the DGT to improve compliance through education and balanced enforcement of regulations.Keywords: E-filing; Freelance Taxpayer Compliance; Tax Knowledge; Tax Sanctions; Taxpayer Awareness